Odpowiedzi

2010-03-09T19:25:33+01:00

b)
0,7x-3 + 1,1x = -2,1x - 0,6
0,7x+1,1x+2,1x=-0,6+3
3,9x=2,4
x=8/13

c)
0,11x-0,08+0,4x= - 0,01x - 0,2
0,11x+0,4x+0,01x=-0,2+0,08
0,52x=-0,12
x=3/13

d)
-0,4 + 2x - 2,1 = 0,3x - 0,8
2x-0,3x=-0,8+0,4+2,1
1,7x=1,7
x=1

e)
0,06x - 1 + 0,4x = 0,27 - 0,04x
0,06x+0,4x+0,04x=0,27+1
0,5x=1,27
x=2,54
Najlepsza Odpowiedź!
  • k95
  • Rozwiązujący
2010-03-09T19:28:11+01:00
B)0,7x-3 + 1,1x = -2,1x - 0,6
0,7x+1,1x+2,1x=-0,6+3
3.9x=2.4/ : 3.9
x=0,61
c)0,11x-0,08+0,4x= - 0,01x - 0,2
0,11x+0,4x+0,01x=-0,2+0,08
0,52x=-12// : (-0,52)
x=0,23
d) -0,4 + 2x - 2,1 = 0,3x - 0,8
2x-0,3x=-0,8+2,1+0,4
1,7x=1,7 // : 1,7
x=1
e) 0,06x - 1 + 0,4x = 0,27 - 0,04x
0,06x+0,04x+0,4=0,27+1
0,5x=1,27 // : 0,5
x=2.54